A Gonadotropin-Releasing Hormone-Like Molecule Modulates the Activity of Diverse Central Neurons in a Gastropod Mollusk, Aplysia Californica - Sun, Biao; Tsai, Pei-San (Frontiers in Endocrinology, 2011)
In vertebrates, gonadotropin-releasing hormone (GnRH) is a crucial decapeptide that activates the hypothalamic-pituitary-gonadal (HPG) axis to ensure successful reproduction. Recently, a GnRH-like molecule has been isolated from a gastropod mollusk, Aplysia californica. This GnRH (ap-GnRH) is deduced to be an undecapeptide, and its function remains to be explored. Our previous study demonstrated that ap-GnRH did not stimulate a range of reproductive parameters. Instead, it affected acute behavioral and locomotive changes unrelated to reproduction. In this study, we used electrophysiology and retrograde tracing to further explore the central role of ap-GnRH. Sharp electrode intracellular recordings revealed that ap-GnRH had diverse effects on central neurons that ranged from excitatory, inhibitory, to the alteration of membrane potential. Unexpectedly, extracellular recordings revealed that ap-GnRH suppressed the onset of electrical afterdischarge (AD) in bag cell neurons, suggesting an inhibitory effect on female reproduction. Lastly, using immunocytochemistry (ICC) coupled with nickel-backfill, we demonstrated that some ap-GnRH neurons projected to efferent nerves known to innervate the foot and parapodia, suggesting ap-GnRH may directly modulate the motor output of these peripheral tissues. Overall, our results suggested that in A. californica, ap-GnRH more likely functioned as a central modulator of complex behavior and motor regulation rather than as a conventional reproductive stimulator.